Goal Instructions, Response Format, and Idea Generation in Groups. (June 2013) - Goldenberg, Olga; Larson, James R.; Wiley, Jennifer
This study examined the separate and joint impact of two standard, but seemingly conflicting brainstorming rules on idea generation in interacting and nominal groups: the free-wheeeling rule, which calls for the production of dissimilar ideas, and the build-on rule, which encourages idea combination and improvement. We also tested whether the superior performance of interacting groups found in several previous studies using a brainwriting technique may have been due to the different response formats employed by groups and individuals. Interacting groups and individuals generated ideas for improving their university under one of three sets of instructions. In one condition, participants were given the build-on rule, but not the free-wheeling rule, and in another condition, the reverse was true. In the third condition, both rules were provided. When the two rules were presented separately, interacting and nominal groups responded similarly, generating ideas from more semantic categories in response to the free-wheeling rule, and generating more practical ideas in response to the build-on rule. But when those rules were presented simultaneously, interacting groups generated ideas from fewer semantic categories than did nominal groups. In addition, interacting groups produced more ideas overall than nominal groups, but only when the two used different response formats.